Treatment of LF slag to prevent powdering during cooling - Ghorai S.; Mandal G.K.; Roy S.; Minj R.K.; Agarwal A.; Singh D.P.; Kumar A.; Ramna R.B.V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The polymorphic transformation of the monoclinic β-polymorph to the orthorhombic γ-polymorph of di-calcium silicate at around 500°C during cooling results in disintegration of slag. The slag generated, during the production of thermo mechanically treated steel in ladle furnace at M/s Tata Steel Limited, Jamshedpur, India, behaves in similar manner. An attempt has been made to prevent the crumbling of ladle furnace slag. The experiments were conducted in 10 kg air induction furnace. Various types of silica source were used to prevent the disintegration of ladle furnace slag by reducing the basicity and optimizing the additives amount. Apart from silica sources, other additives like borax and barium carbonate were also used to stabilize the β phase. Present investigation reveals that disintegration of ladle furnace slag can be prevented either by addition of 0.2% boarx or 2% barium carbonate. Dust formation can also be prevented by decreasing the ladle furnace slag basicity to about 1.7. Toxicity Characteristic Leaching Procedure test, of the borax and barium carbonate treated slag samples, indicates that barium carbonate treated slag cannot be used for the dusting prevention as it contains high level of barium.